2002
DOI: 10.1212/wnl.59.6.841
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of altered consciousness during seizures

Abstract: These findings are consistent with a role for the thalamus and upper brainstem in consciousness mechanisms. The authors suggest that the spread of epileptic discharges or a trans-synaptic activation (diaschisis) of these structures is an important mechanism in the alteration of consciousness during seizures. Variance in the results may be due to differences in timing of radioisotope injection, sensitivity of the subtraction SPECT technique, and the ability to clinically assess the conscious state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(63 citation statements)
references
References 20 publications
4
57
2
Order By: Relevance
“…Pronounced slowing in bilateral frontal and parietal association cortices in patients undergoing complex partial temporal lobe seizures is further evidenced by intracranial EEG recordings taken of these patients [12]. Such findings support the hypothesis that loss of consciousness during temporal lobe seizures may result from focal seizures arising in the medial temporal lobe spreading to midline subcortical structures (upper brainstem -diencephalic activating systems), disrupting their activating function, and thus secondarily leading to widespread inhibition of the frontoparietal cortex [53,61].…”
Section: Epileptic Seizuressupporting
confidence: 67%
“…Pronounced slowing in bilateral frontal and parietal association cortices in patients undergoing complex partial temporal lobe seizures is further evidenced by intracranial EEG recordings taken of these patients [12]. Such findings support the hypothesis that loss of consciousness during temporal lobe seizures may result from focal seizures arising in the medial temporal lobe spreading to midline subcortical structures (upper brainstem -diencephalic activating systems), disrupting their activating function, and thus secondarily leading to widespread inhibition of the frontoparietal cortex [53,61].…”
Section: Epileptic Seizuressupporting
confidence: 67%
“…In general, clinical studies rely on indirect criteria for the measure of consciousness. More recent studies have proposed 2 to 4 criteria to estimate consciousness during seizures [6,7,29,31]. Recently we proposed a 8 criteria scale in order to capture the different elements for a more objective evaluation of the AOC during seizures (Table 1) [1].…”
Section: No Visual Attention (0 or 1)mentioning
confidence: 99%
“…Metabolic neuroimaging studies using ictal SPECT in order to study the increase of cerebral blood flow (CBF) in regions affected by seizures have suggested that secondary involvement of thalamus and/or subcortical structures during seizures plays a determinant role in the impairment of consciousness [6,29].…”
Section: No Visual Attention (0 or 1)mentioning
confidence: 99%
“…LEV-induced suicidal behavior has been reported infrequently with a past history of affective disorders [4][5][6][7]. The authors report an apparent dose/concentration-dependent LEV-induced de novo major depression with near fatal suicide attempt in a patient without prior history of affective disorder.…”
Section: Short Communicationmentioning
confidence: 91%